Theoretical Perspectives and Current Challenges of Outcome-Based Education Framework - Saima Shaheen (International Journal of Engineering Education, 2019)
AbstractOutcome-Based education is a performance-based approach for the curriculum development, a future-oriented learner-centered ‘Empowerment Paradigm’ that empowers and endorses all learners with future success. It is an influential and tempting way of restructuring and reorganizing engineering education. Washington Accord, an International accreditation convention, an independent agreement between signatory organizations to provide an external accreditation to undergraduate engineering programs. The accredited engineering programs that qualify an engineer to enter into the practice of professional engineers are equally recognized and acknowledged by other signatory countries and responsible organizations Pakistan Engineering Council (PEC) is a full signatory to the Washington Accord and a regulatory organization for the accreditation of engineering programs in Pakistan. To keep up the permanent membership status, it is the requirement of PEC to implement Outcome-Based in engineering degree awarding institutes in Pakistan. The main aim of Outcome-Based education in engineering education is to empower engineering students with the essential characteristics required to switch themselves into the engineering profession as a global and professional engineer. The focus of current research is to explore the philosophical and theoretical underpinnings of Outcome-Based education. Moreover, to unveil the current challenges in the implementation of OBE framework in engineering education.